Lattice structure design based on singularity-separated parameterization. (February 2023) - Liao, Yizhou; Zheng, Zhihao; Abdullahi, Hamza Sulayman; Gao, Shuming
Abstract: The lattice structure has not only a high strength-to-weight ratio but also many other important properties, like energy absorption, heat transfer, and the highly unusual properties of metamaterials. In this paper, we present a novel parameterization-based method that can be used to generate optimal 3D lattice structures. First, a frame field is generated from a stress field and smoothed using stress as a weight to reduce and simplify the singularities of the frame field. Second, a singularity-separated parameterization is performed under the guidance of the frame field. Third, struts are generated in both the parameterized region and the separated regions to produce a basic lattice. Then the stress-concentrated areas are enhanced by additional struts. Finally, the radii of all struts are optimized to further improve the stiffness. Compared to methods that do not handle singularities, the lattices, which are generated using our new approach, show less distortion, and they are more streamlined. The FEA results confirm that the new method can indeed be used to improve the stiffness of structures. Highlights: A novel parameterization-based method that generates optimal 3D strut-based lattice structures. A stress-weighted smoothing method to improve the quality of the frame field generated from the stress field. A singularity-separated parameterization which reduces distortion, and is more robust. A structure-enhancing method by adding additional struts according to the stress distribution.